Tracking sero-molecular trends of swine brucellosis in Hawai‘i and the central Pacific - Thi Hai Au La; Ian A. McMillan; Prashant Dahal; Andrew H. Burger; Mahdi Belcaid; Darrin M. Phelps; Samuel M. Goldstein; Vienna R. Brown; Michael H. Norris (Frontiers in Public Health, 2024)
IntroductionBrucellosis is a zoonotic disease of mammals caused by bacterial species of the Brucella genus. The reservoir for disease is typically mammals, with species of Brucella found infecting amphibians, bats, and marine mammals. Brucella spp. can pass directly to humans through contact with infected animals or their products. Brucella spp. can cause chronic debilitating infections in mammals, including humans, and is associated with spontaneous abortions in infected animals, causing reduced fecundity. In Hawai‘i, terrestrial species that could harbor Brucella spp. include swine, cattle, horses, and axis deer among others. The numerous feral swine in Hawai‘i are known to carry Brucella suis, with evidence supporting infections in cattle. Brucella suis also poses infection risk to humans, dogs, and potentially horses across the state.MethodsIn this study, 3,274 feral swine serum samples collected from 5 of the 8 main islands over a 15-year span were analyzed for exposure to B. suis. Of the 558 watersheds in the state, 77 were sampled as part of this effort. Spatial analysis was used to identify watersheds of concern. MLVA and whole genome SNP analysis was used for molecular epidemiological analysis.ResultsStatewide seropositivity rates were triple that of feral swine found in the conterminous United States. Smoothed positivity rates were highest on Maui, followed by O‘ahu, and the island of Hawai‘i. Island-by-island analysis found high brucellosis positivity levels associated with specific watersheds and agricultural areas. Local spatial autocorrelation identified hot spots on O‘ahu and Hawai‘i. MLVA analysis of available B. suis from Hawai‘i found molecular epidemiological connections with B. suis found in French Polynesia and the mainland US while differing from those in Tonga, Western Polynesia. Strains from Hawai‘i are phylogenetically closest to strains from the United States. MLVA and SNP analysis found B. suis strains from Hawai‘i fell into the genetic group that contains biovar 1 B. suis.DiscussionThis work identified islands and watersheds of high brucellosis seropositivity in feral swine of Hawai‘i, highlighting the magnitude of the zoonotic risk. Introduction of strains in recent history is unlikely due to modern animal trade and disease control practices. Genomic analysis of strains in Hawai‘i and the Pacific area can provide hidden historical and local clues to brucellosis epidemiology in the state.